Asia’s Economic Evolution Through the Lens of Bibliometrics - Sarmiento, Allen Grace (Journal of Interdisciplinary Perspectives, 2025)
This study presents a comprehensive bibliometric analysis of economic development research in Asia, using co-citation and co-word techniques to map the field's intellectual and thematic landscape. While many bibliometric studies examine narrow topics, this research addresses a gap by offering a holistic synthesis of the field. The objective of this study is to identify the intellectual structure and thematic evolution of this research domain. Drawing from a curated dataset of peer-reviewed articles from the Scopus database, the analysis identifies seven distinct co-citation clusters and five thematic groupings. Key findings highlight the convergence of research on critical domains, including foreign direct investment (FDI), institutional quality, financial inclusion, and trade integration. The analysis also reveals emerging themes such as sustainability, innovation, and crisis response, underscoring the field's interdisciplinary nature. The resulting intellectual map provides a valuable guide for researchers, policymakers, and students. It clarifies the evolution of development thought, demonstrates the power of bibliometric tools, and helps identify new directions for future, evidence-based inquiry across Asia.